2015
DOI: 10.1007/978-94-017-9849-5_15
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Core Scanners as an Environmental Forensics Tool: A Case Study of Polluted Harbour Sediment (Augusta Bay, Sicily)

Abstract: Since the 1970s the highly industrialised and enclosed Augusta Bay (Sicily) has become internationally recognized as a polluted environment that could represent a hazard to human health. The pollutant of greatest concern, derived from a former chlor-alkali plant, is mercury that exists beyond Intervention Levels in parts of the harbour. The affected areas are also contaminated by other heavy metals and organic compounds (PAHs and PCBs) that were mainly discharged from co-located petrochemical industries. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
(37 reference statements)
2
17
0
Order By: Relevance
“…The elemental distribution in the MG cores (Figs 5, S5, S6, S7 and S8), except for units L1 and L2 (Fig. ), is in line with that reported for the uncontaminated sediments of inner Augusta Bay, which consist primarily of carbonates (Ca and Sr) and clays (Si, K and Rb; Croudace et al ., ) as well as the outcropping geology, dominated by carbonates and volcanoclastics/volcanics within muddy sediments and calcarenites (Grasso & Lentini, ). While the Ca and Sr signatures dominate the marine sediment, due to the occurrence of carbonates (Chagué‐Goff et al ., ), Ti/Ca and Ti/Sr are most likely to reflect the terrigenous input, with Ti sourced from volcanics, gneiss and schists and thus often used as an indicator of terrestrial material in onshore or offshore tsunami deposits (Chagué‐Goff et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elemental distribution in the MG cores (Figs 5, S5, S6, S7 and S8), except for units L1 and L2 (Fig. ), is in line with that reported for the uncontaminated sediments of inner Augusta Bay, which consist primarily of carbonates (Ca and Sr) and clays (Si, K and Rb; Croudace et al ., ) as well as the outcropping geology, dominated by carbonates and volcanoclastics/volcanics within muddy sediments and calcarenites (Grasso & Lentini, ). While the Ca and Sr signatures dominate the marine sediment, due to the occurrence of carbonates (Chagué‐Goff et al ., ), Ti/Ca and Ti/Sr are most likely to reflect the terrigenous input, with Ti sourced from volcanics, gneiss and schists and thus often used as an indicator of terrestrial material in onshore or offshore tsunami deposits (Chagué‐Goff et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, a wide range of contaminants (Hg, Pb, Cu, heavy hydrocarbons, etc.) have been introduced into the harbour since the early 1960s, and have been partially retained in the sediments (Romano et al ., ; Sprovieri et al ., ; Bellucci et al ., ; Croudace et al ., ) due to the contemporary construction of outer breakwaters. The high pollution levels in Augusta Bay (especially for Hg), have presumably caused stressful conditions to Posidonia oceanica , leading to its complete disappearance, as detailed in several studies (Di Leonardo et al ., , , ; Sprovieri et al ., ).…”
Section: Study Sitementioning
confidence: 98%
“…Many researchers continue to use either count or count-rate data as supplied by the instrument's software or they may adopt a semi-empirical approach by analyzing a small number of sub-samples using WD-XRF, ED-XRF or ICP-OES to calibrate their data (e.g. Boyle et al 2015;Croudace et al 2015). A more advanced approach based on the use of multi-variate statistics is described by Weltje et al (2015) and represents a significant advance that could become increasingly used.…”
Section: Numerical and Software Developmentsmentioning
confidence: 99%
“…With their ability to simultaneously and non-destructively measure thirty or more elements (and other co-registered properties such as magnetic susceptibility and a radiographic image), X-ray core scanners have made a significant contribution to the study of marine, estuarine and lacustrine sedimentary sections as well as rocks, coal, speleothems and tree rings (e.g. Croudace et al 2006;Rothwell et al 2006; Thomson et al 2006;Croudace and Rothwell 2010;Rothwell and Croudace 2015;Croudace et al 2015;Kelloway et al 2015). Many of the existing XRF core scanners originated as concepts or prototypes in marine science establishments (universities and research institutions in Holland, UK and Japan) from the 1990s through to the early 2000s.…”
Section: Introductionmentioning
confidence: 99%
“…The counts are not normally matrix corrected and several previous studies have shown that there is a good first approximation to concentration (e.g. Croudace et al 2006Croudace et al , 2015. Users also commonly take small subsamples and analyse using a quantitative destructive method (ICP-OES or WD-XRF) to validate/calibrate Itrax data.…”
Section: Xrf-core Scanningmentioning
confidence: 99%